Analisa Hubungan Perubahan Muka Air Laut, Perubahan Volume Es Di Kutub Selatan Dan Curah Hujan Dengan Menggunakan Satelit Altimetri(Studi Kasus : Laut Selatan Pulau Jawa Tahun 2011 - 2014) - Anjasmara, Ira Mutiara; Hakim, Lukman (GEOID, 2016)
One of the impacts of climate change is sea level change. It is the result of the world's major thawing of coating ice, the North Pole and South Pole. Besidesfrom the effects of change ofice volume , sea level changes greatly influenced by the phenomenon of rain interpreted by rainfall.The effects of sea level change significantly also felt by residents of Indonesia which are predominantly located on the coast.Changes in sea level can be observed by using satellite Altimetry . One of them is the Jason-2 satellites mission. The change ofice volume can also be observed by satellite Altimetry that is through Cryosatmission.While the rainfall measurement, observed by satellite Tropical Rainfall Measuring Mission (TRMM).In this study, the monitoring of sea level change is carried out on the South Java sea in a period of 4 years (2011-2014) by taking three points of observation, namely Bodies Cilacap, Sadeng and Prigi. On the other hand, the monitoring of ice volume is carried out on the Antarctic at the same time. The result of data processing shows the trend of sea level changes in the southern Java with the value of -3,2 mm / year. In contrast, the trend of ice volume change in the South Pole has a value of 206.069 m3/year. The correlation between the value of sea level change s and ice volume change in the South Pole gives the correlation value of 0,044,the correlation values showed aweakThe correlation between the value of sea level changes and changes in rainfall gives the correlation value of of 0.716 (Cilacap), 0.720 (Sadeng), 0.773 (Prigi), the correlation values showed a strong correlation.